14:(2.x+3)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
x=13 nên x+1=14
\(f\left(x\right)=x^{14}-x^{13}\left(x+1\right)+x^{12}\left(x+1\right)-...+x^2\left(x+1\right)-x\left(x+1\right)+14\)
\(=x^{14}-x^{14}-x^{13}+x^{13}-...+x^3+x^2-x^2-x+14\)
=14-x=1
x=13 nên x+1=14
f(x)=x14−x13(x+1)+x12(x+1)−...+x2(x+1)−x(x+1)+14f(x)=x14−x13(x+1)+x12(x+1)−...+x2(x+1)−x(x+1)+14
=x14−x14−x13+x13−...+x3+x2−x2−x+14=x14−x14−x13+x13−...+x3+x2−x2−x+14
=14-x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
|7 - \(\dfrac{3}{4}\)\(x\)| - \(\dfrac{3}{2}\) = \(\dfrac{1}{\dfrac{1}{2}}\)
|7 - \(\dfrac{3}{4}x\)| - \(\dfrac{3}{2}\) = 2
|7 - \(\dfrac{3}{4}\)\(x\)| = 2 + \(\dfrac{3}{2}\)
|7 - \(\dfrac{3}{4}x\)| = \(\dfrac{7}{2}\)
\(\left[{}\begin{matrix}7-\dfrac{3}{4}x=\dfrac{7}{2}\\7-\dfrac{3}{4}x=-\dfrac{7}{2}\end{matrix}\right.\)
\(\left[{}\begin{matrix}\dfrac{3}{4}x=7-\dfrac{7}{2}\\\dfrac{3}{4}=7+\dfrac{7}{2}\end{matrix}\right.\)
\(\left[{}\begin{matrix}\dfrac{3}{4}x=\dfrac{7}{2}\\\dfrac{3}{4}x=\dfrac{21}{2}\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=\dfrac{14}{3}\\x=14\end{matrix}\right.\)
5 - |\(x-3\)| = 5
|\(x-3\)| = 5 - 5
|\(x-3\)| = 0
\(x-3\) = 0
\(x\) = 3
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{2}\cdot\frac{18}{14}+\frac{1}{2}\cdot\frac{3}{14}-\frac{1}{2}\cdot\frac{7}{14}\)
\(=\frac{1}{2}\left(\frac{18}{14}+\frac{3}{14}-\frac{7}{14}\right)\)
\(=\frac{1}{2}\cdot1=\frac{1}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
X+\(\dfrac{2}{7}\)=\(\dfrac{1}{2}\)
X = \(\dfrac{1}{2}\)-\(\dfrac{2}{7}\)
X = \(\dfrac{3}{14}\)
Chọn đáp án A. \(\dfrac{3}{14}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left[\left(3^{14}\times69+3^{14}\times12\right):3^{16}-7\right]:2^4\)
\(=\left[3^{14}\left(69+12\right):3^{16}-7\right]:2^4\)
\(=\left[3^{14}.81:3^{16}-7\right]:2^4\)
\(=\left[3^{14}.3^4:3^{16}-7\right]:2^4\)
\(=\left[3^2-7\right]:2^4\)
\(=2:2^4\)
\(=\dfrac{2}{16}=\dfrac{1}{8}\)
\(\left[\left(3^{14}.69+3^{14}.12\right):3^{16}-7\right]:2^4\\ =\left[3^{14}.\left(69+12\right):3^{16}-7\right]:2^4\\ =\left[3^{14}.81:3^{16}-7\right]:2^4\\ =\left[3^{14}.3^4:3^{16}-7\right]:2^4\\ =\left(3^2-7\right):2^4=2:2^4=\dfrac{1}{2^3}=\dfrac{1}{8}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{2}{5}+\dfrac{3}{5}\cdot\dfrac{10}{3}\cdot\dfrac{1}{2}=\dfrac{2}{5}+\dfrac{10}{5}\cdot\dfrac{1}{2}=\dfrac{2}{5}+1=\dfrac{7}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)